A family for Gracie - Lillard, Amy (Lillard, Amy. Pontotoc Mississippi series., 2019)
Gracie Glick is known for being the helpful one, always available for a relative in need. But now that she<U+2019>s longing for a home and family of her own, it<U+2019>s time to help herself. With few eligible men in Pontotoc, Gracie<U+2019>s choices, and her time, are limited. So she takes a bold leap of faith: she proposes to Matthew Byler, a handsome, recently widowed, father of five. It<U+2019>s not until after they<U+2019>re married that Gracie learns Matthew doesn<U+2019>t want more children . . . With his grief still fresh, and his children needing care while he tends to his farm, Gracie is the answer to Matthew<U+2019>s prayers. But a marriage in name only suits him fine. And when he finally tells Gracie the dismaying reason why, they must decide whether to continue together<U+2014>or apart. It<U+2019>s a choice that will force them both to look deeper into their hearts than ever before . . .